2020
DOI: 10.13057/biodiv/d210810
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution bromeliads plants as breeding habitat for mosquito larvae (Diptera: Culicidae) in Bogor, Indonesia

Abstract: Abstract. Ikhsan M, Hadi UK, Soviana S. 2020. Diversity and distribution bromeliads plants as breeding habitat for mosquito larvae (Diptera: Culicidae) in Bogor, Indonesia. Biodiversitas 21: 3494-3498. Bromeliads leaf structure can hold water and has potential as the breeding ground for mosquitoes. Information regarding the potential of bromeliads as a habitat for mosquito larvae in Indonesia is limited. This study aims to identify the diversity of bromeliads and their potential as breeding habitat for mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…albopictus, Aedes spp., and Cx. quinquefasciatus (Ikhsan et al 2020). Bromeliads are a member of the 50-genus family Bromeliaceae, with more than 2,500 species (Ikhsan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…albopictus, Aedes spp., and Cx. quinquefasciatus (Ikhsan et al 2020). Bromeliads are a member of the 50-genus family Bromeliaceae, with more than 2,500 species (Ikhsan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus (Ikhsan et al 2020). Bromeliads are a member of the 50-genus family Bromeliaceae, with more than 2,500 species (Ikhsan et al 2020). However, only two species of Bromeliads are found in Mantup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…albopictus, Ae. aegypti, Aedes spp., Armigeres subalbatus , and Culex quinquefasciatus were found on bromeliads of the genera Neoregelia, Cryptanthus , and Alcantarea [ 19 ]. Other studies have identified that Ae.…”
Section: Environmental Methodsmentioning
confidence: 99%
“…This ornamental plant has a problem when the weather is hot and exposed to sunlight where the tips of the leaves evaporate too much water to wilt. High survival rates up to 80% but very low aesthetic value due to abnormal symptoms such as dry leaf atrophy (Phonpho et al, 2019;Ikhsan, et al, 2020) Objects identified number 6 via google lens received a perfect rating with a score of 3 because the genus and species were immediately identified as Neoregelia marmorata on the first search. The intralingual translation of the three searches above is very well identifiable where Neoregelia marmorata is synonymous with the names Aregelia marmorata and also has common names as Baker, Marbled bromeliad and Marbleplant.…”
mentioning
confidence: 99%